L’Heure du Gospel. Liminalité, identité et religion dans un bar gay - Edward R. Gray; Scott Thumma (Genre, Sexualité et Société)
Published in the United States for the first time in 1996 by two doctors of Religious Studies at Emory (Atlanta), this article analyzes an innovative gay ritual outside of religious institutions. The « Gospel Hour » is the name taken up in an Atlanta gay bar for a regular session of gospel singing on Sunday, led by a troupe of drag queens with varied religious beliefs, and frequented by men reviving the evangelical Protestantism of their childhood. Mobilizing the concept of « liminality » inherited from anthropologist Victor Turner, the authors analyze this as a moment of ritual community creation, on the border of the religious and the profane, and the border between Christian socializations and gay sociabilities.